Cooperacion regional latinoamericana en el campo de la comunicacion : necesidades experiencias y posibilidades (SELA CaracasVE, 1986)
Discusses reasons for regional cooperation in area of communication and the occurence of this activity in the global process of development and integration in Latin America. Describes areas of communication where regional cooperation needs to be a priority. Analyses regional cooperation in various areas such as research and highlights main difficulties which impede their success or led to failure. Discusses role of government organizations in cooperation in communication. Indicates some mechanisms and existing institutions in the region that can effectively contribute to the development of cooperation activities in communication in the future.
Bibliography: p. 82-86